PENGARUH KUALITAS AUDIT DAN KEPEMILIKAN KELUARGA TERHADAP AUDIT REPORT LAG (ARL) - Shofaa Haniifah; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2020)
This study aims to examine empirically the relation between two dimensions of audit quality, namely auditor industry specialization, auditor reputation, and family ownership on audit report lag. The dependent variable used is audit report lag. The independent variables used are auditor industry specialization, auditor reputation, and family ownership. The control variables used are leverage, subsidiary, and loss.The data that was used in this study was secondary data and selected by using purposive sampling method. The sample size is 62 consists of 31 mining companies listed in Indonesia Stock Exchange period 2017 and 2018. The analytical method used in this study was multiple linear regression analysis with the help of the SPSS version 23 computer program.The results of this study prove that auditor reputation negatively influences to the audit report lag, while the auditor industry specialization and family ownership has no influence to the audit report lag.